PELAYANAN PROSES BELAJAR - MENGAJAR BERBASIS WEB - Putro, Endi (Teknik dan Ilmu Komputer, 2012)
Learning is a process of behavior change that can get from knowledge penetrating. So, educate is process to guide, to direct, and to manage learning process. Learning and educate is a process to manage method and resources to change behavior. Formally, learning and educate is transformation process from lecture to participant. Managing method and resources is did to make class more effective. One way how to manage is preparing resources that will be used. Technically, resources is placed on web media where lectures give resources and participant can get it. Resources is being prepare on web used to support learning and educate process.ÃÂ Keywords: learning, educate, web